Cost Effectiveness and Efficiency of Reusing Single-use Medical Devices - Aan Santi; Risa Ismadewi; TR Fitriyani; Murdani Abdullah (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2014)
Background: Reusing single-use medical devices is a very important and complicated process since theimplementation requires both operational and technical skills, even for professional users. The aim of our studywas to determine the cost effectiveness and efficiency of reusing single-use medical devices. Method: The study was a cross-sectional study conducted between July and December 2013. It compared twogroups of patients who underwent endoscopic retrograde cholangiopancreatography (ERCP) examination at the Digestive Endoscopy Center, Cipto Mangunkusumo Hospital, Jakarta. Patients in the first group received new single-use medical devices; while patients in the other group received the re-used single-use medical devices.Reprocessing for reusing single-used medical devices was conducted according to standard procedures ofdecontamination and sterilization. Results: Reusing medical devices were more commonly found (50.9%) in ERCP procedures than usingnew medical devices (49.1%). There was no significant difference on operator satisfaction between using there-used and new medical devices (p = 0.062). There was lower average cost for reusing medical devices thanusing new medical devices (IDR 198,818,250.00 vs. IDR 594,354,000.00; p = 0.000); percentage of successrate for reusing was lower than new medical devices (80% vs. 90,6%; p = 0.203). There was also no significantdifference regarding the negative impacts such as fever or infection of reusing medical devices compared tousing new medical devices (p = 0.676). Conclusion: This study has shown good effectiveness in terms of operator satisfaction, success rate andimpacts on patients. The cost for reusing medical devices is more efficient than using new medical devices.Keywords: effectiveness, efficiency, reusing medical devices, new, endoscopy ABSTRAKLatar belakang: Penggunaan alat medis sekali pakai (single-use) yang dipakai kembali (re-use) menjadi sangat penting dan kompleks dalam menerapkan kemampuan operasional dan teknik pada profesional penggunaalat tersebut. Tujuan penelitian ini adalah untuk menilai efektifitas biaya dan efisiensi penggunaan perangkatmedis single-use yang dijadikan re-use. Metode: Penelitian ini merupakan penelitian potong lintang dilakukan pada Juli hingga Desember2013. Penelitian membandingkan dua kelompok pasien yang menjalani pemeriksaan endoscopic retrogradecholangiopancreatography (ERCP) di Pusat Endoskopi Saluran Cerna (PESC), Rumah Sakit CiptoMangunkusumo, Jakarta. Pasien pada kelompok pertama menerima tindakan dengan alat medis baru; sedangkanpasien di grup lainnya menerima tindakan dengan alat medis re-use. Proses penggunaan alat medis re-use dilakukan sesuai dengan prosedur dekontaminasi dan sterilisasi yang berlaku. Hasil: Penggunaan alat medis dalam tindakan ERCP lebih banyak menggunakan alat re-use (50,9%) dibandingkan alat baru (49,1%); kepuasan operator pada alat re-use maupun alat baru tidak berbeda secarasignifikan (p = 0,062); rata-rata biaya pada penggunaan alat re-use lebih rendah dibandingkan pada alat baru (Rp 198.818.250,00 vs. Rp 594.354.000,00; p = 0.000); persentase keberhasilan penggunaan alat re-use lebihrendah dibandingkan pada alat baru (80% vs. 90,6%; p = 0,203); dampak berupa terjadi demam atau infeksipada penggunaan alat re-use dan alat baru tidak menunjukkan perbedaan yang signifikan (p = 0,676). Simpulan: Penggunaan alat re-use menunjukkan efektifitas yang baik pada kepuasan operator, keberhasilanalat, dan dampak pada pasien. Biaya penggunaan alat re-use lebih efisien dibanding dengan penggunaan alatbaru.Kata kunci: efektifitas, efisiensi, perangkat medis re-use, baru, endoskopi